Sympatric speciation in structureless environments. Issue 1 (December 2016) - Getz, Wayne; Salter, Richard; Seidel, Dana; Hooft, Pim
Abstract Background Darwin and the architects of the Modern Synthesis found sympatric speciation difficult to explain and suggested it is unlikely to occur. Increasingly, evidence over the past few decades suggest that sympatric speciation can occur under ecological conditions that require at most intraspecific competition for a structured resource. Here we used an individual-based population model with variable foraging strategies to study the evolution of mating behavior among foraging strategy types. Initially, individuals were placed at random on a structureless resource landscape, with subsequent spatial variation induced through foraging activity itself. The fitness of individuals was determined by their biomass at the end of each generational cycle. The model incorporates three diallelic, codominant foraging strategy genes, and one mate-choice orm -trait (i.e. incipient magic trait) gene, where the latter is inactive when random mating is assumed. Results Under non-random mating, them -trait gene promotes increasing levels of either disassortative or assortative mating when the frequency ofm respectively increases or decreases from 0.5. Our evolutionary simulations demonstrate that, under initial random mating conditions, an activatedm -trait gene evolves to promote assortative mating because the system, in trying to fit a multipeak adaptive landscape, causes heterozygous individuals to be less fit than homozygous individuals. Conclusion Our results extend our theoretical understanding that sympatric speciation can evolve under nicheless or gradientless resource conditions: i.e. the underlying resource is monomorphic and initially spatially homogeneous. Further the simplicity and generality of our model suggests that sympatric speciation may be more likely than previously thought to occur in mobile, sexually-reproducing organisms.